Interaction between living bone particles and rhBMP‐2 in large segmental defect healing in the rat femur. Issue 12 (25th April 2016) - Liu, Fangjun; Wells, James W.; Porter, Ryan M.; Glatt, Vaida; Shen, Zhenxin; Schinhan, Martina; Ivkovic, Alan; Vrahas, Mark S.; Evans, Christopher H.; Ferreira, Elisabeth
ABSTRACT: Orthopedic surgeons sometimes combine recombinant, human BMP‐2 with autograft bone when dealing with problematic osseous fractures. Although some case reports indicate success with this off‐label strategy, there have been no randomized controlled trials. Moreover, a literature search revealed only one pre‐clinical study and this was in a cranial defect model. The present project examined the consequences of combining BMP‐2 with particles of living bone in a rat femoral defect model. Human bone particles were recovered with a reamer‐irrigator‐aspirator (RIA). To allow acceptance of the xenograft as surrogate autograft, rats were administered an immunosuppressive cocktail that does not interfere with bone healing. Implantation of 200 µg living bone particles generated a small amount of new bone and defects did not heal. Graded amounts of BMP‐2 that alone provoked no healing (1.1 µg), borderline healing (5.5 µg), or full healing (11 µg) were added to this amount of bone particles. Addition of BMP‐2 (1.1 µg) increased osteogenesis, and produced bridging in 2 of 7 defects. The combination of BMP‐2 (5.5 µg) and bone particles made healing more reliable and advanced the maturation of the regenerate. Bone formation with BMP‐2 (11 µg) and bone particles showed improved maturation. Thus, the combination of autograft and BMP‐2 may be helpful clinically under conditions where the healing response is suboptimal. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:2137–2145, 2016. Clinical significance These data support the clinical use of recombinant, human BMP‐2 with autograft bone when treating large segmental osseous defects. The combination leads to greater bone formation and accelerates the maturation of the regenerate.